2020
DOI: 10.5114/hm.2020.94197
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-session reliability of a pedal force system for power output and pedal force effectiveness measurements

Abstract: Purpose. The study assessed within-and between-session reliability of power output (PO) and pedal force effectiveness and compared PO from the pedals with the Lode Excalibur cycle ergometer. Methods. Seventeen male cyclists performed 10 trials at 3 levels of PO (1.5, 2.5, and 3.5 W/kg) and 3 cadences (60, 80, and 100 rpm) in 2 sessions. Instrumented pedals and a portable motion tracking system were synchronized to collect pedal forces and 3D full body motion, respectively. PO and the index of effectiveness (IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…10 Two-dimensional (Powerforce) or three-dimensional (JA: Ped3; I-crank system, Sensix, Poitiers, France; Forped, Cycling Science, d.o.o., Ljubljana, Slovenia) dynamometric pedals have been used in the literature to measure pedal forces. [50][51][52][53][54] Authors have shown that the I-crank system provides accurate measurements of crank torque, power output and mechanical work output. 53 However, Bini and Hume have observed that this system is reliable to measure power output and IE within a given session, but variability in data increased between two sessions, probably due to the repositioning of the motion tracking sensors.…”
Section: Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Two-dimensional (Powerforce) or three-dimensional (JA: Ped3; I-crank system, Sensix, Poitiers, France; Forped, Cycling Science, d.o.o., Ljubljana, Slovenia) dynamometric pedals have been used in the literature to measure pedal forces. [50][51][52][53][54] Authors have shown that the I-crank system provides accurate measurements of crank torque, power output and mechanical work output. 53 However, Bini and Hume have observed that this system is reliable to measure power output and IE within a given session, but variability in data increased between two sessions, probably due to the repositioning of the motion tracking sensors.…”
Section: Kineticsmentioning
confidence: 99%
“…53 However, Bini and Hume have observed that this system is reliable to measure power output and IE within a given session, but variability in data increased between two sessions, probably due to the repositioning of the motion tracking sensors. 54 In addition, instrumented bicycle crank systems, which can be used for laboratory and field tests (Axis Cranks, Swift Performance, Australia), allow accurate measurements of 2D pedal forces on both the left and right crank arms independently. 55 As mentioned previously, these systems are often used in scientific studies to measure IE (Eq.…”
Section: Kineticsmentioning
confidence: 99%